EFEKTIVITAS MEDIASI SEBAGAI UPAYA DALAM PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL (STUDI DI DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI KALIMANTAN BARAT) - U M A R.SH A.2021141007, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2016)
ABSTRACTThis thesis discusses the effectiveness of mediation as an effort in resolving industrial disputes (Studies in the Department of Manpower and Transmigration of West Kalimantan Province). The method used in this study is a socio-juridical approach. From the results of this thesis can be concluded that factors that contributed to the industrial dispute was the clarity of the status of workers and have included social security, reneged on the agreement PKWT so shall reimburse Rp. 3 million under the terms of the agreement, do not want in the transfer to other parts, is married to fellow employees, the clarity of the worker's status is asked for the change of status from non-permanent to permanent workers, and disciplinary problems that do not come to work without giving details or without permission. Most of the factors that led to the emergence of industrial disputes in the region of West Kalimantan is absent from work without giving details. The role of mediator in resolving industrial relations disputes can be said to be good because it can be completed by consensus. It can be seen from the results of the settlement, the more the result is the Collective Agreement as many as 29 cases, rather than the result Prompts Written as many as 12 cases. Implementation of mediation in the Office of Manpower and Transmigration of West Kalimantan Province also can be said is good because in accordance with the settlement procedures contained in Law No. 2 of 2004 concerning Industrial Relations Dispute Settlement. Barriers faced mediator in resolving industrial relations disputes is due to the absence of the entrepreneur himself but was represented by staff personnel that may hinder the process of mediation for employers' representatives must report to the employer prior session, the workers who make the minutes of talks with giving false information made- make as if employers do not want to be invited to negotiate and cooperate, and workers are not orderly administration by not including a power of attorney if authorized. Recommendations from the study of this thesis is the need for a mediator to bring the parties directly without the entrepreneur may be represented so as not to slow down the process of dispute resolution. Even if represented, party authorized to be given the authority to make decisions in the mediation process so that the mediation process is completed quickly. It is expected to workers in order to complete the administration by presenting a power of attorney if authorized so be orderly administration.Keywords: Effectiveness of Mediation, as an Effort, Dispute Settlement, Industrial Relations.ABSTRAKTesis ini membahas efektivitas mediasi sebagai upaya dalam penyelesaian perselisihan hubungan industrial (Studi Di Dinas Tenaga Kerja Dan Transmigrasi Provinsi Kalimantan Barat). Metode pendekatan yang digunakan dalam penelitian ini adalah pendekatan yuridis-sosiologis. Dari hasil penelitian tesis ini diperoleh kesimpulan Bahwa Faktor-faktor yang menyebabkan timbulnya perselisihan hubungan industrial adalah kejelasan status pekerja dan minta diikutsertakan jamsostek, mengingkari isi perjanjian PKWT sehingga wajib mengganti uang Rp. 3 juta sesuai isi perjanjian, tidak mau di mutasi ke bagian lain, menikah dengan sesama karyawan, kejelasan status pekerja yaitu minta perubahan status dari harian lepas ke pekerja tetap, dan masalah indisipliner yaitu tidak masuk kerja tanpa memberikan keterangan atau tanpa ijin. Sebagian besar faktor yang menyebabkan timbulnya perselisihan hubungan industrial di wilayah Kalimantan Barat adalah tidak masuk kerja tanpa memberikan keterangan. Peranan Mediator dalam menyelesaikan perselisihan hubungan industrial dapat dikatakan baik karena dapat menyelesaikan secara musyawarah mufakat. Hal tersebut bisa dilihat dari hasil penyelesaian, lebih banyak hasilnya adalah Perjanjian Bersama yaitu sebanyak 29 kasus, daripada yang hasilnya Anjuran Tertulis yaitu sebanyak 12 kasus. Pelaksanaan mediasi di Kantor Dinas Tenaga Kerja dan Transmigrasi Provinsi Kalimantan Barat juga bisa dikatakan sudah baik karena sesuai dengan prosedur penyelesaian yang ada dalam Undang-undang Nomor 2 Tahun 2004 tentang Penyelesaian Perselisihan Hubungan Industrial. Hambatan yang dihadapi Mediator dalam menyelesaikan perselisihan hubungan industrial adalah karena tidak hadirnya pengusaha sendiri tetapi diwakilkan oleh staf personalia sehingga bisa menghambat proses mediasi karena wakil pengusaha harus melaporkan hasil sidang kepada pengusaha terlebih dahulu, adanya pekerja yang membuat risalah perundingan palsu dengan memberikan keterangan yang dibuat-buat seolah-olah pengusaha tidak mau diajak berunding dan bekerja sama, dan pekerja tidak tertib administrasi dengan tidak menyertakan surat kuasa jika dikuasakan. Rekomendasi dari penelitian tesis ini adalah perlunya mediator mendatangkan pihak pengusahanya langsung tanpa boleh diwakilkan sehingga tidak memperlambat proses penyelesaian perselisihan. Kalaupun diwakilkan, pihak yang diberi kuasa harus diberi kewenangan untuk membuat keputusan dalam proses mediasi sehingga proses mediasi cepat selesai. Diharapkan kepada pekerja agar melengkapi administrasi dahulu dengan menyertakan surat kuasa apabila dikuasakan sehingga bisa tertib administrasi.Kata Kunci: Efektivitas Mediasi, Sebagai Upaya, Penyelesaian Perselisihan, Hubungan Industrial.